The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1161/circulationaha.112.120501
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Echocardiography Is Essential for Intraoperative Assessment of Mitral Regurgitation

Abstract: Since its introduction, 3-dimensional (3D) transesophageal echocardiography (TEE) has become widely adopted in operating rooms and cardiac catheterization laboratories worldwide. This is because the matrix-array 3D TEE probe allows acquisition of high-quality 3D images in real time with relatively little training. The rapid adoption of this technology has proven that this innovative imaging modality provides additional clinical information beyond that obtained from 2-dimensional (2D) TEE images. These developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Unlike 2D techniques, which require multiple tomographic views to examine the different parts of the mitral valve leaflets, real-time 3D echocardiography provides a comprehensive assessment of the mitral valve in only one view, the "en face" view from the left atrium (surgeon's view, Fig. 3) or the LV, leading to more effective communication with cardiac surgeons [23]. Several studies have demonstrated, at the time of surgery (surgical inspection), the superiority of 3D over 2D echocardiography [24,25].…”
Section: Reparabilitymentioning
confidence: 99%
“…Unlike 2D techniques, which require multiple tomographic views to examine the different parts of the mitral valve leaflets, real-time 3D echocardiography provides a comprehensive assessment of the mitral valve in only one view, the "en face" view from the left atrium (surgeon's view, Fig. 3) or the LV, leading to more effective communication with cardiac surgeons [23]. Several studies have demonstrated, at the time of surgery (surgical inspection), the superiority of 3D over 2D echocardiography [24,25].…”
Section: Reparabilitymentioning
confidence: 99%
“…7,8 Since that time, the role of 3D-TEE in detailed imaging assessment of not only mitral regurgitant severity but also complex mitral anatomic details has become indisputable. 9 As we enter the next phase of transcatheter mitral valve interventions of new repair and replacement devices as well as standardization of transcatheter paravalvular leak (PVL) closure, the role of imaging is evolving. MDCT and 3D-TEE are currently being used to screen patients anatomically for transcatheter mitral valve replacement.…”
Section: See Articles By Suh Et Al and Mak Et Almentioning
confidence: 99%
“…Three-dimensional TOE of the MV is superior to 2D TOE in identifying the precise location and extent of leaflet prolapse and presence of deep clefts, for assessing geometry of the MV annulus and for quantifying MR severity when there are multiple or eccentric jets 18 19. Three-dimensional TOE is now the preferred method for quantifying mitral stenosis, since 3D planimetry accurately defines the MV orifice; measurements are reproducible, with close correlation with invasive and surgical measurements of MV area;20 long-term outcome data using 3D TOE data are awaited.…”
Section: Toe In Clinical Practicementioning
confidence: 99%